(untitled) (International relations and international law Journal, 2026)
This article examines France’s economic diplomacy in Kazakhstan in the context of Central Asia ongoing geo-economic transformation driven by global sanctions fragmentation, the restructuring of international supply chains, and the reconfiguration of trade and logistics routes. Particular attention is paid to the growing strategic role of Central Asia and to Kazakhstan’s position as a key transit, investment, and institutional hub linking Europe and Asia, especially within the framework of the Trans-Caspian International Transport Route (Middle Corridor). The aim of the study is to identify the main directions, instruments, and features of France’s economic diplomacy in Kazakhstan after 2022 and to assess its role in advancing both national and EU-level economic interests in the region. The research focuses on institutional mechanisms, foreign direct investment flows, the involvement of French companies in infrastructure and industrial projects, and the normative dimension of France’s external economic strategy. The methodology combines a qualitative case study approach with the analysis of official policy documents, statistical data on foreign direct investment and trade, and content analysis of strategic statements. The findings demonstrate that France’s economic diplomacy in Kazakhstan has evolved from predominantly resource-based and project-oriented engagement toward a model of strategic economic partnership focused on infrastructure development, industrial cooperation, sustainable energy, and integration into regional value chains. The study contributes to the academic literature by offering a comprehensive analysis of France’s economic diplomacy in Kazakhstan under conditions of geo-economic instability. Its practical relevance lies in providing insights for policymakers and practitioners involved in external economic strategy, investment promotion, and international cooperation. Keywords: economic diplomacy; France–Kazakhstan relations; Central Asia; Middle Corridor; geo-economics.